Construction, Genotypic and Phenotypic Characterization, and Immunogenicity of Attenuated ΔguaBA Salmonella enterica Serovar Typhi Strain CVD 915 - Wang, Jin Yuang (American Society for Microbiology, 2001)
A promising live attenuated typhoid vaccine candidate strain for mucosal immunization was developed by introducing a deletion in the guaBA locus of pathogenic Salmonella enterica serovar Typhi strain Ty2. The resultant ΔguaBA mutant, serovar Typhi CVD 915, has a gene encoding resistance to arsenite replacing the deleted sequence within guaBA, thereby providing a marker to readily identify the vaccine strain. CVD 915 was compared in in vitro and in vivo assays with wild-type strain Ty2, licensed live oral typhoid vaccine strain Ty21a, or attenuated serovar Typhi vaccine strain CVD 908-htrA (harboring mutations in aroC, aroD, and htrA). CVD 915 was less invasive than CVD 908-htrA in tissue culture and was more crippled in its ability to proliferate after invasion. In mice inoculated intraperitoneally with serovar Typhi and hog gastric mucin (to estimate the relative degree of attenuation), the 50% lethal dose of CVD 915 (7.7 × 10(7) CFU) was significantly higher than that of wild-type Ty2 (1.4 × 10(2) CFU) and was only slightly lower than that of Ty21a (1.9 × 10(8) CFU). Strong serum O and H antibody responses were recorded in mice inoculated intranasally with CVD 915, which were higher than those elicited by Ty21a and similar to those stimulated by CVD 908-htrA. CVD 915 also elicited potent proliferative responses in splenocytes from immunized mice stimulated with serovar Typhi antigens. Used as a live vector, CVD 915(pTETlpp) elicited high titers of serum immunoglobulin G anti-fragment C. These encouraging preclinical data pave the way for phase 1 clinical trials with CVD 915.